2012
DOI: 10.4103/0973-6247.95048
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of Treponemal and non-Treponemal test for screening of blood donated at a blood center

Abstract: The non-Treponemal tests such as Rapid Plasma Reagin test (RPR) or the Venereal Disease Reference Laboratory test are the most commonly used test for screening of syphilis in the blood centers in India. Now, with the availability of Enzyme-linked immunosorbent assay (ELISA) and Immunochromatographic assays in the market, we decided to evaluate these assays in comparison with Treponema pallidum Haemagglutination Assay (TPHA) which was considered as a gold standard for this study. A total of 8 685 samples of vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
13
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 14 publications
(22 reference statements)
4
13
2
2
Order By: Relevance
“…One of the study[ 4 ] from western region of our country showed 56.4% false positivity of RPR in blood donors as compared with 60% in our study further indicating impact of RPR on the discard rate of the blood bank.…”
supporting
confidence: 56%
“…One of the study[ 4 ] from western region of our country showed 56.4% false positivity of RPR in blood donors as compared with 60% in our study further indicating impact of RPR on the discard rate of the blood bank.…”
supporting
confidence: 56%
“…8 The sensitivity of TPHA is 85 to 100% and the specificity is 98 to 100%. 9 In females, the asymptomatic Chlamydial infection, if left untreated leads to Pelvic Inflammatory Disease (PID), infertility and its complications. Henceforth, screening women for Chlamydia trachomatis helps in prevention of PID, ectopic pregnancy and infertility.…”
mentioning
confidence: 99%
“…Many comparative studies on this subject have suggested that there are many advantages of using a reverse algorithm, in which the screening starts with a treponemal test (7)(8)(9)(10)(11). The use of treponemal immunoassays for syphilis screening eliminates biologically false positives due to the presence of anticardiolipin antibodies in certain diseases (12)(13)(14). In addition, immunoassays can be automated, their results are objective, and they reduce labor costs and increase laboratory efficiency (3, 7-10).…”
Section: Resultsmentioning
confidence: 99%